Remote training of medical students: advantages and disadantages - Petryshen, O. I.; Hrytsiuk, M. I.; Chornenka, Zh. A.; Halysh, I. V. (Journal of Education, Health and Sport, 2020)
Modern medical education, its quality requires the use of innovative transformations in training technology. The use of modern information technologies allows us to transfer the learning process to a qualitatively higher level. As a result, traditional education is reoriented to a fundamentally new level, where the student’s role changes: he becomes an active participant in the educational process.